Building Organizational Resilience in MSMEs: Does Strategic Agility Work Through Organizational Learning - Ahmad Johan; Tanty Sondari; Ayke Nuraliati (Journal of Management and Creative Business, 2026)
This study aims to analyze the role of organizational learning mediation in the relationship between strategic agility and organizational resilience in Micro, Small, and Medium Enterprises (MSMEs) in Bandung, West Java. The research method used a quantitative survey with 150 MSME owners/managers selected through purposive sampling techniques. Data analysis was carried out with Partial Least Squares Structural Equation Modeling (PLS-SEM) using a bootstrapping procedure. The results of the study support all the hypotheses proposed. Strategic agility has been proven to have a direct positive effect on organizational resilience and also a positive effect on organizational learning. Furthermore, organizational learning has a positive effect on organizational resilience. Important findings show that organizational learning plays a role as a partial mediator in the relationship between strategic agility and organizational resilience. This research contributes in the form of a mediation model that can be tested to build the resilience of MSMEs in the context of West Java. The practical implications emphasize that strategic adaptability needs to be transformed through the organizational learning process in order to increase the resilience capacity of MSMEs to face the dynamics of the business environment.